Efektivitas Model Means Ends Analysis (MEA) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP: (The Effectiveness of the Means Ends Analysis (MEA) Model on the Mathematical Problem-Solving Ability of Junior High School Students) - Siti Gita Permana (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: This study aims to identify the increase and influence of the application of the means ends analysis (MEA) model in learning mathematics on students' mathematical problem-solving abilities. This research was conducted at a state junior high school in Karawang, West Java, Indonesia. Methodology: The research method used is a quasi-experimental method with the Nonrandomized Control Group Pretest–Posttest Design. The sample of this research was 80 students consisting of 40 students for the experimental class and 40 students for the control class. Determination of the sample was carried out using a purposive sampling technique in seventh grade. Data collection after treatment was carried out using a mathematical problem-solving test instrument. Findings: The results of the study revealed that the average mathematical problem-solving ability of students who were taught by the means ends analysis model was higher than that of students who were taught by direct learning. Significance: In addition, the means ends analysis (MEA) model has an influence on mathematical problem-solving abilities with a large effect. The conclusion of this study is that the means ends analysis model is effective in improving students' mathematical problem-solving abilities.   Abstrak Tujuan: Penelitian ini bertujuan untuk mengidentifikasi peningkatan dan pengaruh penerapan model means ends analysis (MEA) dalam pembelajaran matematika terhadap kemampuan pemecahan masalah matematis siswa. Penelitian ini dilakukan di salah satu SMP Negeri di Karawang, Jawa Barat, Indonesia. Metodologi: Metode penelitian yang digunakan adalah metode quasi eksperimen dengan desain Nonrandomized Control Group Pretest–Posttest. Sampel penelitian ini adalah 80 siswa yang terdiri dari 40 siswa untuk kelas eksperimen dan 40 siswa untuk kelas kontrol. Penentuan sampel dilakukan dengan menggunakan teknik purposive sampling pada kelas tujuh. Pengumpulan data setelah perlakuan dilakukan dengan menggunakan instrumen tes pemecahan masalah matematis. Temuan: Hasil penelitian mengungkapkan bahwa rata–rata kemampuan pemecahan masalah matematis siswa yang diajarkan dengan model means ends analysis lebih tinggi dari pada siswa yang diajarkan dengan pembelajaran langsung. Signifikan: Selain itu, model means ends analysis (MEA) memiliki pengaruh terhadap kemampuan pemecahan masalah matematis dengan efek yang besar. Kesimpulan hasil penelitian ini adalah bahwa model means ends analysis efektif dalam meningkatkan kemampuan pemecahan masalah matematis siswa.